Representing the Unrepresentable: The Photographs of Lee Miller at Buchenwald and Dachau - Sáez de Urabain, Ainara Miguel (Historia y Comunicación Social, 2016)
This article proposes a reflection on what the historian Saul Friedlander called “the limits of representation” of the massacres and genocides, in order to provide evidence to help settle the old debate about the Holocaust unrepresentability. To achieve this, we will carry out a textual analysis of five of the most painful images that the American photographer Lee Miller realized in the Nazi concentration camps of Buchenwald and Dachau, in April 1945. The war correspondent, who had been Man Ray’s assistant photographer, muse and lover, witnessed the horror, and if she knew how to represent it, that was, in a great extent, thanks to its surreal look.